Review Of The Role Of Paralegals Regarding Violence Against Woman And Children In Cilandak Barat And Lebak Bulus Urban Villages - Loren Ghazalah; Yusup Hidayat (Fakultas Hukum Dehasen, 2024)
Women and children, being the most vulnerable to environmental violence, often have their rights overlooked due to various factors. Law No. 16 of 2011 on Legal Aid was enacted to ensure the equitable provision of legal assistance, aiming to maximize the involvement of Advocates who infrequently offer free aid through paralegals. This research, utilizing socio-legal research methods, examines the paralegal's role in reducing violence against women and children in West Cilandak and Lebak Bulus Villages. Based on the research findings from interviews and observations, linked to the theory of effectiveness, it can be concluded that the paralegal's role in minimizing violence against women and children in West Cilandak and Lebak Bulus Villages has not proven to be effective.